2021
DOI: 10.1088/2058-6272/ac3476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma treatment on the seed germination and seedling growth of radish (Raphanus sativus)

Abstract: The effect on the germination and seedling growth of radish (Raphanus sativus) seeds were examined employing a dielectric barrier discharge (DBD) at atmospheric pressure and room temperature for various treatment time. DBD plasma using argon gas of flow rate 2 l m−1 was employed in this study. Radish seeds were treated with DBD plasma for 1–5 min, respectively. Germination characteristics, seedling growth parameters, the contact angle of the seed coat, water uptake capacity, mass loss, the temperature of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…As shown in Figure 1 , accelerated germination was observed, which is in line with the growth enhancement effects observed in other studies [ 4 , 41 ]. Growth enhancement is not the only type of plant response to plasma and also includes seed surface functionalization, seed decontamination, as well as stress anddefense response [ 1 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 1 , accelerated germination was observed, which is in line with the growth enhancement effects observed in other studies [ 4 , 41 ]. Growth enhancement is not the only type of plant response to plasma and also includes seed surface functionalization, seed decontamination, as well as stress anddefense response [ 1 ].…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that seed germination can be accelerated, or the plant properties can be altered where root length, shoot length, harvest mass or stress and disease resistance have increased after plasma treatment [ 4 , 5 ]. Despite the numerous successful results obtained in other studies, it remains elusive which plasma treatment parameters are required to affect plant growth parameters mainly because of the plethora of physical, chemical, and biological variables [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It indicates the amount of time it takes for a seed to germinate or emerge [36,37]. The mean germination time was determined using equation (3).…”
Section: The Mean Germination Time (Mgt)mentioning
confidence: 99%
“…Worldwide food shortage has been increased with increasing industrialization, urbanization, infrastructure, and insufficient land structure and natural resources. And for that, the main challenge is to search for a single viable and cost-effective solution that can be applied to overcome the challenge of modern food scarcity [2,3]. In contemporary research, the focus is given to the development of plasma-treated seeds and to meet the challenges to increase food production and ensure food safety.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the interdisciplinary approaches, cold plasma treatment is now identified as a viable solution for enhancing the seed sprouts and subsequent plant growth for crops such as radish, wheat, tomato, and soybean. [1][2][3][4][5][6][7][8][9] Apart from being advantageous for agricultural use, enhancement of the sprouting rate of seeds through nonthermal plasma techniques is beneficial for the food processing industry. [10][11][12] It has generally been accepted that, by boosting seed germination and plant cultivation rates, the global demand may be efficiently satisfied.…”
Section: Introductionmentioning
confidence: 99%